Psicología para todos: Entendiendo la conducta humana - Vigoa Escobedo, Yisell (2025)
The book “Psychology for Everyone: Understanding Human Behavior” is a comprehensive treatise that presents a systematic approach to the study of psychology, integrating its epistemological foundations, theoretical frameworks, and research methodologies. The work develops an evolutionary analysis of the discipline, tracing its progression from its philosophical roots to its establishment as an empirical science, examining the fundamental paradigms that have shaped its development: psychoanalytic theory, behaviorism, cognitive psychology, and the humanistic approach.